Determinants of time trade-off valuations for EQ-5D-5L health states: data from the Canadian EQ-5D-5L valuation study - Sayah, Fatima Al (Quality of Life Research, 2016)
Background Previous studies suggest that population subgroups have different perceptions of health, as well as different preferences for hypothetical health states. Objective To identify determinants of health states preferences elicited using time trade-off (TTO) for the 5-level EQ-5D questionnaire (EQ-5D-5L) in Canada. Methods Data were from the Canadian EQ-5D-5L Valuation Study, which took place in Edmonton, Hamilton, Montreal, and Vancouver. Each respondent valued 10 of 86 hypothetical health states during an in-person interview using a computer-based TTO exercise. The TTO scores were the dependent variable and explanatory variables including age, sex, marital status, education, employment, annual household income, ethnicity, country of birth, dwelling, study site, health literacy, number of chronic conditions, previous experience with illness, and self-rated health. Results Average [standard deviation (SD)] age of respondents (N = 1209) was 48 (17) years, and 45 % were male. In multivariable linear regression models with random effects, adjusted for severity of health states and inconsistencies in valuations, older age [unstandardized regression coefficient (β) = -0.077], male sex (β = 0.042), being married (β = 0.069), and urban dwelling (β = -0.055) were significantly associated with health states scores. Additionally, participants from Edmonton (β = -0.124) and Vancouver (β = -0.156), but not those from Hamilton, had significantly lower TTO scores than those from Montreal. Conclusions Socio-demographic characteristics were the main determinants of preferences for EQ-5D-5L health states in this study. Interestingly, preferences were significantly lower in western Canadian cities compared to eastern ones, bringing into question whether a single preference algorithm is suitable for use in all parts of Canada.